Nirmatrelvir‐ritonavir therapy and COVID‐19 vaccination improve clinical outcomes of SARS‐CoV‐2 Omicron variant infection. Issue 2 (26th January 2023) - Qi, Tangkai; Jin, Yinpeng; Wang, He; Liao, Yixin; Liu, Tiefu; Mao, Enqiang; Li, Feng; Li, Yinchuan; Fan, Xiaohong; Ling, Yun
Abstract: To evaluate the effect of Nirmatrelvir‐ritonavir therapy and coronavirus disease 2019 (COVID‐19) vaccination on clinical outcomes of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Omicron infection, we retrospectively analyzed the clinical data of 762 adult patients with confirmed Omicron BA2.2 variant infection, of them 488 patients received standard therapy and 274 patients received Nirmatrelvir‐ritonavir therapy. Subjects were matched by propensity score matching using R language, the baseline factors were balanced by the nearest‐neighbor matching method and were compared, together with the factors including progression to severe/critical disease, viral clearance time, length of hospital stay, and virological rebound of SARS‐CoV‐2 infection. Nirmatrelvir‐ritonavir therapy significantly accelerated viral clearance at Days 14 and  28 during hospitalization, but it had no impact on disease progression, length of hospital stay, or infection rebound. In contrast, COVID‐19 vaccination before admission was positively correlated with the viral clearance rate and negatively correlated with disease progression in a dose‐dependent way. COVID‐19 vaccination reduced the probability of infection rebound. Other factors such as the number of comorbidities, pneumonia on‐admission, and high D2 levels were positively correlated with disease progression. Our study strongly recommended booster COVID‐19 vaccination for the elderly population, particularly patients with comorbidities to prevent critical disease.